ChemInform Abstract: Structural, Vibrational and Electrical Properties of Ordered Double Perovskite Oxide BaLaMnSbO6. Issue 15 (15th April 2014) - Bharti, Chandrahas; Sen, A.; Chanda, Sadhan; Sinha, T. P.
Abstract BaLaMnSbO6 is successfully synthesized by calcination of stoichiometric amounts of BaCO3, La2O3, MnO, and Sb2O5 (alumina crucible; 1.